Pengembangan Bahan Ajar Mata Kuliah IPA Berbasis Pendekatan Scientific Approach: Development of Science Course Teaching Materials Based on the Scientific Approach - Pribowo, Fitroh Setyo Putro (Pedagogia : Jurnal Pendidikan, 2017)
Scientific Approach is one instructional approach used in the curriculum of 2013. That prompted LPTK to generate prospective teachers who understand the essence of the curriculum of 2013. Based on observations activity and low student motivation to learn science. LKS assumed teaching materials can enhance the activity and motivation of students in the learning process. Research conducted by the method of research and development (research and development). Development of research methods used in this study adapt the model ADDIE. This model consists of five main phases or stages: 1) analyze, 2) design, 3) develop, 4) implement, 5) Evaluate. LKS development results-oriented IPA 1 aprroach by expert scientific learning technology obtained a score of V = 87.5 (very valid), while the practicality of the product gained a score of V = 71.5 with practicality criteria quite well. The effectiveness of the product was assessed by increased activity and student motivation. Activities students obtain a score of 73.21 with the active category as well as the motivation to study obtained a score of 63.94 with a category quite well. student worksheets produced meet the elements of a valid, practical, and effective.